3D Seed-Germination-Like MXene with In Situ Growing CNTs/Ni Heterojunction for Enhanced Microwave Absorption via Polarization and Magnetization - Li, Xiao; You, Wenbin; Xu, Chunyang; Wang, Lei; Yang, Liting; Li, Yuesheng; Che, Renchao (Nano-Micro Letters, 2021)
Ti3C2Tx MXene is widely regarded as a potential microwave absorber due to its dielectric multi-layered structure. However, missing magnetic loss capability of pure MXene leads to the unmatched electromagnetic parameters and unsatisfied impedance matching condition. Herein, with the inspiration from dielectric-magnetic synergy, this obstruction is solved by fabricating magnetic CNTs/Ni hetero-structure decorated MXene substrate via a facile in situ induced growth method. Ni2+ ions are successfully attached on the surface and interlamination of each MXene unit by intensive electrostatic adsorption. Benefiting from the possible “seed-germination” effect, the “seeds” Ni2+ grow into “buds” Ni nanoparticles and “stem” carbon nanotubes (CNTs) from the enlarged “soil” of MXene skeleton. Due to the improved impedance matching condition, the MXene-CNTs/Ni hybrid holds a superior microwave absorption performance of − 56.4 dB at only 2.4 mm thickness. Such a distinctive 3D architecture endows the hybrids: (i) a large-scale 3D magnetic coupling network in each dielectric unit that leading to the enhanced magnetic loss capability, (ii) a massive multi-heterojunction interface structure that resulting in the reinforced polarization loss capability, confirmed by the off-axis electron holography. These outstanding results provide novel ideas for developing magnetic MXene-based absorbers. Highlights: 1 Benefiting from the possible “seed-germination” effect, the “seeds” Ni2+ grow into “buds” Ni nanoparticles and “stem” carbon nanotubes (CNTs) from the enlarged “soil” of MXene skeleton. 2 Compared with the traditional magnetic agglomeration, the MXene-CNTs/Ni hybrids exhibit the highly spatial dispersed magnetic architecture. 3 3D MXene-CNTs/Ni composites hold excellent microwave absorption performance (−56.4 dB at only 2.4 mm).